A Potential Role for mu-Opioids in Mediating the Positive Effects of Gratitude - Henning, Max; Fox, Glenn R.; Kaplan, Jonas; Damasio, Hanna; Damasio, Antonio (Frontiers in Psychology, 2017)
Gratitude is a complex emotional feeling associated with universally desirable positive effects in personal, social, and physiological domains. Why or how gratitude achieves these functional outcomes is not clear. Toward the goal of identifying its' underlying physiological processes, we recently investigated the neural correlates of gratitude. In our study, participants were exposed to gratitude-inducing stimuli, and rated each according to how much gratitude it provoked. As expected, self-reported gratitude intensity correlated with brain activity in distinct regions of the medial pre-frontal cortex associated with social reward and moral cognition. Here we draw from our data and existing literature to offer a theoretical foundation for the physiological correlates of gratitude. We propose that mu-opioid signaling (1) accompanies the mental experience of gratitude, and (2) may account for the positive effects of gratitude on social relationships, subjective wellbeing, and physiological health.